2019
DOI: 10.1136/bmjqs-2018-008995
|View full text |Cite
|
Sign up to set email alerts
|

Altering standard admission order sets to promote clinical laboratory stewardship: a cohort quality improvement study

Abstract: BackgroundCareful design of preprinted order sets is needed to prevent medical overuse. Recent work suggests that removing a single checkbox from an order set changes physicians’ clinical decision-making.Local problemDuring a 2-month period, our coronary care unit (CCU) ordered almost eight times as many serum thyroid-stimulating hormone (TSH) tests as our neighbouring intensive care unit, many without a reasonable clinical basis. We postulated that we could reduce inappropriate testing and improve clinical la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…We found that the updated admission form enables a sustainable reduction in laboratory tests seen in previous studies translated to BUN blood tests at these Canadian teaching hospitals. [11][12][13][14][15][16][17] Additionally, because of the simplicity of the intervention implementation where the physician leaders communicated the rationale for the form update, the common pitfalls of completing a physician led QI project, that requires several hours of dedicated time for physicians to review the shortcomings of the current processes while simultaneously focusing on their clinical duties was avoided. 31 The greater reductions experienced at hospital A compared with hospital B indicate that the additional interventions such as the targeted resident education, unit process changes alerting physicians of lab test order frequency and posted BUN clinical indication job aides that were in place at hospital A had a compounding effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the updated admission form enables a sustainable reduction in laboratory tests seen in previous studies translated to BUN blood tests at these Canadian teaching hospitals. [11][12][13][14][15][16][17] Additionally, because of the simplicity of the intervention implementation where the physician leaders communicated the rationale for the form update, the common pitfalls of completing a physician led QI project, that requires several hours of dedicated time for physicians to review the shortcomings of the current processes while simultaneously focusing on their clinical duties was avoided. 31 The greater reductions experienced at hospital A compared with hospital B indicate that the additional interventions such as the targeted resident education, unit process changes alerting physicians of lab test order frequency and posted BUN clinical indication job aides that were in place at hospital A had a compounding effect.…”
Section: Discussionmentioning
confidence: 99%
“…8 9 Significant reductions in laboratory ordering have been reported through interventions of education and job aides, to redesigning standard admission order sets, laboratory forms or software as well as multimodal approaches. [10][11][12][13][14][15][16][17] There can be risks associated with these interventions that target reductions in laboratory test order such as physicians under ordering when clinically required and missing possibly relevant information for the patients diagnosis or management. 18 The blood urea nitrogen (BUN) test or the urea test is commonly ordered with creatinine, often adding little value to patient management at significant cost.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the fact that RUNIT negative patients also experienced a lower rate of duplicate studies suggests that the change in ordering J o u r n a l P r e -p r o o f pattern was adopted and applied outside the protocol, a feature associated with other successful initiatives. 22,23 This culture change was likely the main cause of the reduction in TTE ordering, highlighting the importance of not only the intervention, but also education endeavors including our audit, feedback, and grand rounds.…”
Section: Discussionmentioning
confidence: 99%
“…28 Furthermore, Leis et al showed that simple removal of a check box for a thyroid-stimulating hormone (TSH) order from a critical care unit admission order set significantly decreased inappropriately ordered TSH tests from 60.6 to 20%. 29 This study is unique in that it sought to assess the effects of several different types of order sets changes outside of modifying the default settings of an order. Order set design is an important area of study as computerized provider order entry (CPOE) with CDS can lead to unintended consequences that need to be monitored for after implementation.…”
Section: Discussionmentioning
confidence: 99%